先化简,再求值:(xy-x^2)÷x^2-2xy+y^2/xy*x-y/x^2,其中x=2009,y=2010
1个回答
(xy-x^2)÷[(x^2-2xy+y^2)/xy]*(x-y)/x^2
=-x(x-y)*[xy/(x-y)^2]*(x-y)/x^2
=-y
y=2010
=-2010
相关问题
先化简再求值 [2x(x^2y-xy^2)+xy(xy-x^2)]÷x^2y 其中=x2008 y=2004
先化简,再求值:[(xy+2)(xy-2)-2(x²y²-2)]÷xy,其中x=10,y=-1/25
先化简再求值:xy^3÷(-xy)+(x+2y)(x-2y),其中x=根号2,y=1
先化简在求值[2x(x^2y-xy^2)+xy(xy-x^2)]÷(x^2y),其中x=2008,y=2007
先化简再求值(x²+xy-2y²)/(x²-2xy+y²)
先化简再求值:(x-y/x)÷[x-(2xy-y^2/x)],其中x=2013
先化简再求值,3xy²(xy+2y²-x²)+3x³y²,其中x=2,
先化简再求值:2x²+(-x²+3xy+2y²)-(-x²-xy+2y²
先化简,再求值3x²y-[2xy²-2(xy-3/2x²y)+2xy]-2x²y
先化简,再求值;(x^2y-x^3)\(x^2+2xy+y^2)÷x\(x-y)×(x+y)\(x^2-2xy+y^2)